A bio-inspired fractal microchannel heat sink with secondary modified structure and sub-total-sub fluid transmission mode for high heat flux and energy-saving heat dissipation. (March 2023) - Ma, Chuangbei; Sun, Yunna; Wu, Yongjin; Zhang, Qingze; Wang, Yan; Ding, Guifu
Highlights: A bio-inspired fractal microchannel heat sink is proposed and fabricated for high heat flux and energy-saving heat dissipation. With leaf-like secondary structure, heat sink reduces pressure drop and improves coefficient of performance than traditional fractal microchannel heat sink. The addition of sub-total-sub fluid transmission mode reduces the maximum temperature rise and improves coefficient of performance and uniformity of temperature. The heat flux of 577 W cm −2 can be dissipated by using the pumping power of 1.3 mW with the maximum temperature rise of 60 K, which coefficient of performance exceeds 40, 000. Abstract: With the rapid integration and miniaturization of electronic devices, thermal management has become one of the key factors restricting the development of microelectronic devices. The existing cooling methods consume enormous water and energy and destroy the environment and ecology. Therefore, a new heat dissipation technology is needed to meet the dual requirements of high heat flux heat dissipation capacity (HFHDC) and low power consumption. Inspired by the natural mass and energy transport ability of fractal structure, a composite microchannel with fractal microchannel serving as the main structure and secondary modified structure is proposed in this work to maintain high HFHDC and greatly reduce energy consumption of heat dissipation. Furtherly, a fluid guided layer providing high fluid distribution and lower pressure drop is designed to re-collect the distributed fluid at the end of the microchannel and discharge the cooling water. Compared with traditional design with single outlet, the temperature uniformity distribution can be improved and the pressure drop can be reduced by 46%. The simulation results show that under the temperature rise of 60 K, the heat flux of 577 W cm −2 (total heat power of 57.7 W) can be extracted by using the pumping power of 1.3 mW, and the coefficient of performance is as high as 43, 465. This optimized design is fabricated by micro-machining processes, and the experiment data matches well with the simulation results. This work possesses high HFHDC, guarantees the trend of miniaturization of electronic system and greatly reduces the energy consumption for heat dissipation, providing a reference for low-power heat dissipation methods.